Case Report: Three Case Reports of Rapidly Progressive Dementias and Narrative Review (2022)
Rapidly progressive dementia (RPD) is a heterogeneous group of diseases characterized by cognitive impairment and other neurological disorders developed in a short span of fewer than 2 years. Currently viewed as new and infrequent entities, most medical personnel have little understanding of it. Nevertheless, they significantly compromise many patients’ quality of life. Here, we drive 3 clinical cases that evolve as RPD with different etiologies. Case 1: 70-year-old woman presented to the emergency with neuropsychiatric syndrome for 18 days. The researchers identified inflammatory cerebrospinal fluid (CSF), protein 14-3-3-positive T-tau protein, MRI: T2 and FLAIR hyperintensities in bilateral caudate nuclei with diffusion restriction, EEG shows a generalized periodic pattern with triphasic wave morphology. Case 2: 29-yearold man with cognitive impairment and faciobrachial dystonia seizure. The diagnosis was confirmed by achieving elevated antibodies against voltage-gated potassium channels. Case 3: A 49-year-old woman with encephalopathy and myoclonic seizures; EEG and MRI showed subtle changes. The patient also had a normal CSF but a positive CBA serologic NMDA-R antibody test. We described fundamental aspects of RPD to allow made differential diagnoses in patients with cognitive impairment and encephalopathy. Establishing an early and accurate diagnosis can benefit patients with RPD etiologies that are treatable and even reversible, decreasing in morbidity and mortality.